Pyrolyzed Bio Charcoal Briquettes Of Solid Waste From Lhokseumawe Patchouli Oil Refinery - Zainuddin Ginting; Khairul Anshar; Adi Setiawan; Ishak Ishak; Chalisna Wildani; Sri Widia Santika; Cut Riski Milya (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
The availability of petroleum fuels derived from fossils is decreasing along with the increase in the human population. This study aims to create bio-charcoal briquettes derived from solid waste of patchouli oil refining. Research on the use of the by-products of the pyrolysis process on solid waste from patchouli oil refining for making bio charcoal briquettes was carried out using temperature variables of 300, 350 and 400 °C, raw material weights of 600, 1200, and 1800 grams and pyrolysis time variables of 60, 90, 120 and 150 minutes. Solid waste has first been cut into small sizes, dried in the sun first, and then put into a pyrolysis device to be carbonized according to predetermined variables. The results of pyrolysis were then put into a desiccator to cool for 30 minutes and then tested for moisture content, ash content, fly content, bound carbon content, calorific value, SEM test, and combustion rate. The best research results obtained were at a temperature of 400 °C, a raw material weight of 600, and a time of 150 minutes with a thermal value of 5,291 cal/g, a moisture content of 5.77%, an ash content of 4.28%, a volatile matter content of 9.11% and a bound carbon content of 77.42% and a combustion rate of 0.1841 grams/minute. The obtained calorific value shows that patchouli solid waste bio charcoal can be used as an alternative fuel that can be renewed and fulfills SNI 01-6235-2000.